Potencial zoonótico da ascaridiose humana e suína: aspectos moleculares, morfológicos e filogenéticos das espécies Ascaris lumbricoides e Ascaris suum - Fernando Sergio Barbosa (2015)
Ascaris lumbricoides, Linnaeus, 1759 and Ascaris suum, Goeze, 1782, are nematode parasites that were described primarily infecting humans and swines. A. lumbricoides it is the most prevalent parasite in humans, and it is part of a severe public health, manly in subdeveloped countries. Already A. suum is considered one of the most important helminthes in swines, causing loss of weight and late development of those animals. Although A. lumbricoides and A. suum infect preferably and respectively humans and swines, the zoonotic nature of those parasites is not clarified. On this context, the current research aimed differ those parasites through and morphologic and molecular aspects, evaluate the natural infection of humans by A. suum and analyze the phylogeny of those parasites in different regions of Brazil and in Lima, Peru. Furthermore, the research also aimed to evaluate the potential of swine experimental infection by A. lumbricoides and human experimental infection by A. suum. In the morphological analysis of those parasites, the serrated denticles present on the edge of the parasite lips were analyzed in scanning electron microscopy and optical microscopy. It was observed that the serrated denticles in A. lumbricoides presented concave extremities and in A. suum the denticles presented triangular extremities. In the molecular analysis was drawn specific primers for the mitochondrial genes COXI and ITS1 of Ascaris spp., which allowed , after amplification of the expected segments, differentiate A. lumbricoides of A. suum. In the process of finding humans naturally infected by A. suum, residences nearly swines farms were visited and samples of faeces from the dwellers were collected. After morphological and molecular analysis of parasites, it was found that one individual was infected with A. suum. Finally, phylogenetic analysis of the collected specimens demonstrated homogeneity between the two species. The results observed in this study contribute to the distinction of the species that can affect humans and especially, for the understanding of the epidemiology of parasitosis.